New Perspectives on the Bank-Firm Relationship Lending, Management and the Impact of Basel III - Ferretti, Paola (Palgrave Macmillan Studies in Banking and Financial Institutions, 2016)
This book analyses the connections between the banking industry in Europe and the companies it finances. Ferretti specifically studies how these bonds have evolved over time and questions whether now is the time for a change in the relationship's dynamics. Chapters discuss the role of bank lending in firms' financing during the recent financial crisis, as well as issues in credit risk management. The discussion also examines regulatory requirements impacting banks and firms (Basel III) and how they intersect with banks' internal purposes. Moreover, the book explores how the financial crisis has impacted the relationship between banks and businesses, and seeks to identify the strengths and weaknesses inherent to it. Through this timely discussion, Ferretti looks to the future of the relationship between banks and non-financial organizations to see how they can be revitalised, adapted and reimagined in a post-crisis economy.